Meningkatkan Efisiensi Manajemen Armada dan Mengurangi Unit yang Tidak Dapat Digunakan di PT Serasi Logistics Indonesia Improving Fleet - Saribanon, Euis; Sihotang, Thobias Oktrian; Pahrudin, Cecep; Ashari, Yogi; Nugroho, Agus (Jurnal Abdimas Transportasi & Logistik, 2024)
The logistics industry, particularly road freight transportation, plays a crucial role in ensuring the smooth distribution of goods in Indonesia. PT Serasi Logistics Indonesia (SELOG) faces significant challenges in fleet management, especially concerning the high rate of units not ready for operation (UTSP), which affects operational efficiency and the ability to meet urgent demand. This community service activity aims to improve the efficiency of fleet management at SELOG and reduce the UTSP ratio through the implementation of a structured management system and data-driven technology. The methods used in this activity include data collection through direct observation, interviews, and analysis of the existing fleet management system. The results of this activity show a significant reduction in the UTSP ratio from 15% to 6% within two months after the implementation of a more scheduled fleet maintenance system and demand forecasting system based on data. Additionally, improving coordination between divisions successfully enhanced the response to urgent requests. This activity contributes significantly to the development of logistics management, particularly in fleet maintenance and the use of technology to enhance operational efficiency.